2014
DOI: 10.1161/atvbaha.114.303422
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress–Initiated Signaling and Its Regulation of Endothelial Function

Abstract: Atherosclerosis develops preferentially at branches and curvatures of the arterial tree, where blood flow pattern is disturbed rather than being laminar, and wall shear stress has an irregular distribution without defined directions. The endothelium in the atherosusceptible regions, in comparison to that in atheroresistant regions, shows activation of pro-proliferative and pro-inflammatory gene expressions, reduced production of nitric oxide (NO), increased leukocyte adhesion and permeability, as well as other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
374
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 450 publications
(385 citation statements)
references
References 95 publications
(122 reference statements)
9
374
0
2
Order By: Relevance
“…Although ICAM-1 expression showed a milder induction than VCAM-1, av siRNA completely suppressed Although acute onset of flow provides an easily reproducible model for shear stress signaling, endothelial cells at atherosclerosis-prone sites in vivo are chronically exposed to disturbed flow patterns. To determine whether integrinspecific signaling similarly regulates the chronic inflammation seen in disturbed flow models, a5 and av knockdown HAECs were exposed to oscillatory shear stress (model of disturbed flow 2,8 ) for 18 hours. Similar to the onset of flow, knockdown of av integrins but not a5 integrins inhibited flowinduced VCAM-1 ( Figure 3G) and ICAM-1 protein expression ( Figure 3H).…”
Section: Flow-induced Inflammation Requires Avb3mentioning
confidence: 99%
See 3 more Smart Citations
“…Although ICAM-1 expression showed a milder induction than VCAM-1, av siRNA completely suppressed Although acute onset of flow provides an easily reproducible model for shear stress signaling, endothelial cells at atherosclerosis-prone sites in vivo are chronically exposed to disturbed flow patterns. To determine whether integrinspecific signaling similarly regulates the chronic inflammation seen in disturbed flow models, a5 and av knockdown HAECs were exposed to oscillatory shear stress (model of disturbed flow 2,8 ) for 18 hours. Similar to the onset of flow, knockdown of av integrins but not a5 integrins inhibited flowinduced VCAM-1 ( Figure 3G) and ICAM-1 protein expression ( Figure 3H).…”
Section: Flow-induced Inflammation Requires Avb3mentioning
confidence: 99%
“…Although traditional risk factors for atherosclerosis, such as hypercholesterolemia and hyperglycemia, are systemic throughout the circulation, atherosclerotic plaques form at discrete areas of the vasculature where vessel geometry results in altered hemodynamics. 1,2 Endothelial cells respond to the frictional force generated by these flow patterns, termed shear stress, and convert them into intracellular biochemical signals that critically modulate endothelial cell function. In straight regions of arteries, shear stress generated by unidirectional, laminar flow promotes nitric oxide production and limits endothelial cell activation, consistent with the absence of atherosclerosis in these areas.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the straight part of the arteries, endothelial cells (ECs) are exposed to laminar blood flow with high shear stress that protects these parts of the vessels from atherogenesis, whereas in the branches and curvatures, the ECs experiencing disturbed flow with reciprocating and low shear stress stimulate the smooth muscle cells (SMCs) within the tunica media to become proliferative and migratory. The activated SMCs migrate into the intima, where they come into close contact with ECs and undergo phenotypic changes to lead to atherosclerosis (2). We recently demonstrated that vascular ECs repress expressions of forkhead box O3, B-cell lymphoma 2, and insulin receptor substrate 1 in the adjacent SMCs by producing microRNA-126-3p (miR-126-3p), and hence induce SMC turnover, and that the application of atheroprotective laminar shear (LS) at 12 dynes/cm 2 to ECs inhibits this paracrine effect (3).…”
mentioning
confidence: 99%